Eating Raoul - Bartel, Paul 1938-2000; Begley, Ed 1949-; Henry, Buck 1930-2020 (Twentieth Century Fox Film Corporation, 2012)
A bawdy, gleefully amoral tale about a prudish married couple feeling put upon by the swingers who live in their apartment building, who, one night by accident, discover a way to simultaneously realize their dream of opening a little restaurant and rid themselves of the 'perverts' down the hall
DVD, NTSC region 1, widescreen (1.78:1) presentation; PCM mono. - Originally produced as a motion picture in 1982. - Special features: audio commentary featuring Richard Blackburn, Robert Schulenberg and Alan Toomayan; The secret cinema and Naughty nurse, two short films by director Paul Bartel; Cooking up Raoul, a making-of documentary; gag reel outtakes; archival interview with Bartel and Woronov; trailer; Folded sheet insert with essay by film critic David Ehrenstein
Orig.: USA, 1982
Keywords: Cannibalism / Drama; Restaurateurs / Drama; Spouses / Drama; Ehepaar; Kannibalismus; Restaurator; Kriminalfilm; Film; DVD-Video